Do pediatricians routinely perform genitourinary examinations during well-child visits? A review from a large tertiary pediatric hospital. Issue 4 (August 2019) - Gerber, J.A.; Balasubramanian, A.; Jorgez, C.J.; Shukla, M.A.; Jacob, J.S.; Zhu, H.; Sheth, K.R.; Mittal, A.; Tu, D.D.; Koh, C.J.; Janzen, N.; Wang, M.-H.; et al.
Summary: Background: The male genital examination is a common source of discomfort for the patient and medical provider. Performance of male genital examination is imperative; however, as many treatable diagnoses can be made. Undescended testicles (UDTs), hernias, testicular tumors, and urethral abnormalities are all potentially concerning findings which can be discovered on routine examination. Objective: The objectives of this study are to determine the rate at which general pediatricians perform routine genitourinary (GU) examinations in the pediatric population and to determine the rate at which UDT are diagnosed or documented in the patient's history. The authors hypothesize the rate of pediatric GU examination during routine well-child visits to be in line with the previously reported rates in the adult literature. Study design: Nine hundred ninety-six consecutive male well-child visits conducted by general pediatricians at the study institution were reviewed. These visits were evaluated for documentation of a detailed GU examination as well as the presence of UDT from these examinations. In addition, past medical and surgical histories were reviewed to determine if a diagnosis of UDT was noted. Results: Pediatricians at the study institution documented GU examinations 99.1% of the time during male well-child visits. Only 1.1% of the cohort had a documentation of UDT at any time point. Of the 11 patients with UDT, 6 boys (54.5%) had spontaneous descent with no referral to urology, whereas 5 (45.5%) required orchidopexy. Discussion: Prior reports suggest 70–75% of routine office visits include a genital examination. None of these reports reviewed the pediatric population, thus making this review novel in this respect. In addition, the results are vastly different from these prior studies as the authors demonstrated over 99% of male well-child examinations included documentation of a thorough genital examination. A limitation of the study is its retrospective nature, which creates a lack of standardization across the data set. In addition, without being physically present in the examination room, one cannot discern whether an examination is simply being documented without actual performance because of the template format of the electronic medical record (EMR). Furthermore, the study was not designed to best evaluate the true rate of UDTs; therefore, the reported rate of 1.1% cannot be accurately associated with a particular age at diagnosis. Conclusions: Pediatricians do, in fact, document GU examinations on a routine basis. This finding cannot be taken with complete certainty as verification of actual examination performance is impractical. While the data demonstrated a lower than expected rate of UDT, depending upon age at diagnosis, this could indicate that although examinations are being documented, their accuracy may be diminished because of various factors at play in the healthcare system as a whole, including improper exam performance and EMR templates. Follow-up studies are required to verify these potentially changing rates of UDT and to determine if there is discordance between documentation and performance of GU examinations.